Combined Li-He isotopes in Iceland and Jan Mayen basalts and constraints on the nature of the North Atlantic mantle - Magna, T; Wiechert, U; Stuart, F; Halliday, A; Harrison, D (2011)
Lithium (Li) isotopes are thought to provide a powerful proxy for the recycling of crustal material, affected by low temperature alteration, through the mantle. We present Li isotope compositions for basaltic volcanic rocks from Hengill, Iceland, and Jan Mayen in order to examine possible links between ocean island volcanism and recycled oceanic crust and to address recent suggestions that mantle 3He/4He is also related to recycling of ancient slabs. Basaltic glasses spanning a range of chemical enrichment from the Hengill fissure system define an inverse correlation between δ7Li (3.8-6.9‰) and 3He/4He (12-20 RA). The high-3He/4He basalts have low δ18O as well as excess Eu and high Nb/U, but carry no Li isotope evidence of being the product of recycling of altered slab or wedge material. In fact, there is no clear correlation between Li or He isotopes on the one hand and any of the other fingerprints of recycled slab components. The low-3He/4He samples do have elevated Nb/U, Sr/Nd, positive Eu anomalies and high δ7Li (∼6.9‰), providing evidence of a cumulate-enriched source that could be part of an ancient altered ocean floor slab. Basalts from Jan Mayen are characterized by large degrees of enrichment in incompatible trace elements typical of EM-like basalts but have homogeneous δ7Li typical of depleted mantle (3.9-4.7‰) providing evidence for a third mantle source in the North Atlantic. It appears that oceanic basalts can display a wide range in isotope and trace element compositions associated with recycled components whilst exhibiting no sign of modern surface-altered slab or wedge material from the Li isotope composition. © 2010 Elsevier Ltd.